Self-Brand Connection: a Literature Review and Directions for Further Research - Seminari, Ni Ketut; Rahyuda, I Ketut; Sukaatmaja, I Putu Gde; Sukawati, Tjok Gde Raka (JDM (Jurnal Dinamika Manajemen), 2022)
Various studies have been conducted to investigate self-brand connections in influencing consum- ers to form brand associations. The authors organized and synthesized the literature on self-brand connections to analyze 20 published articles in the last 25 years over-identification of similarities, in- consistencies, investigation of different conceptualizations of self-brand connections, boundary con- ditions of self-brand connections on brand associations, psychological mechanisms of self-brand connections, theoretical foundations of self-brand connections, and methodological approaches of self-brand connections used in prior literature. The objective of this study is to outlines avenues for opportunities in future research based on previous research.